Modeling context with graph annotations - Bottoni, Paolo; Parisi-Presicce, Francesco (Electronic Communications of the EASST, 2012)
Organisational policies are often formed of declarational (defining constraints on functional services) and operational (realising functionalities via simple activities) aspects. However, when several perspectives are involved, constraints and operations can comprise different aspects, without identifying the origin of some details. We propose the use of annotations as a way to flexibly add and remove application conditions on rules, while maintaining an indication of their origin. We use graph transformations to model operations in some application domain, graph constraints to model conditions imposed by some external domain, and annotations to combine domains. We explore the problem of failure of transactions due to the additional constraints imposed by the contextual domain, and describe a way to redefine the success conditions for transactions employing the modified rules.